Single‐incision totally extraperitoneal inguinal hernia repair is safe and feasible in elderly patients: A single‐center experience of 365 procedures. Issue 4 (18th May 2016) - Wakasugi, Masaki; Tei, Mitsuyoshi; Anno, Kana; Mikami, Tsubasa; Tsukada, Ryo; Koh, Masahiro; Furukawa, Kenta; Suzuki, Yozo; Masuzawa, Toru; Kishi, Kentaro; Tanemura, Masahiro; Akamatsu, Hiroki
Abstract: The aim of this study was to evaluate the feasibility and safety of SILS for totally extraperitoneal inguinal hernia repair in elderly patients. A retrospective analysis of 365 patients who underwent of SILS for totally extraperitoneal inguinal hernia repair from January 2012 to November 2015 at Osaka Police Hospital was performed, and the outcomes of patients aged <80 years and those aged ≥80 years were compared. There was a greater proportion of patients with an ASA score ≥3 among those ≥80 years than among those <80 years. The mean operative time for unilateral inguinal hernia was 94 min in patients <80 years and 98 min in patients ≥80 years. The mean operative time for bilateral inguinal hernia was 133 min in patients <80 years and 130 min in patients ≥80. Intraoperative bleeding was minimal in all patients. Conversion to a different operative procedure occurred in 3% (10/322) of patients <80 years and in 5% (2/43) of patients ≥80 years ( P = 0.6). The mean postoperative hospital stay was 2.2 days for patients <80 years and 2.2 days for patients ≥80 years. The mean follow‐up period 21 ± 14 months (range, 3–50 months) for patients <80 years and 17 ± 14 months (range, 3–50 months) for patients ≥80 years ( P = 0.3). Postoperative complications were seen in 12% (38/322) of patients <80 years and in 14% (6/43) of patients ≥80 years ( P = 0.7). A seroma was seen in 9% (28/322) of patients <80 years and in 12% (5/43) of patients ≥80 years ( P = 0.6). A wound infection occurred in 2% (8/322) of patients <80 years. These seromas and wound infections were managed conservatively. Pulmonary embolism was seen in one patient <80 years (0.3%). There was no mortality or recurrence in either group. SILS for totally extraperitoneal inguinal hernia repair has good cosmesis and can be performed in elderly patients with acceptable morbidity and mortality.